"Dedykacja trzem Królestwom" – opis i znaczenie siedemnastowiecznego pansoficznego manuskryptu Jana Amosa Komeńskiego dla rozwoju nauki - Hampl , Lubomír (Siedleckie Zeszyty Komeniologiczne seria Pedagogika, 2021)
The author presents to the Polish-speaking reader a little-known work by Jan Amos Comenius, titled Latin Dedicatio ad tria regna – Czech Dedikace třem královstvím – Polish Dedykacja trzem Królestwom – English Dedication to the Three Kingdoms. It acquaints us not only with its structure, composition and layout, but also with the main theses and assumed plans. It introduces us to a large extent to the subject matter of „repairing human things”. We see how Jan Amos Comenius persistently and with unprecedented persistence decidedly pursued the honorable goal that he set for himself – the panophilic repair of all human things. A picture of Comenius' hopes for these three European countries, ie Poland, Sweden and Great Britain, was also presented. We also learn how this manuscript in question was gradually modified by him over the course of the seventeenth century. An important fact is also that the described work is important for modern science, especially in historical, social, pedagogical, philological and theological disciplines.